Petrologic and chronological characteristics and formation mechanism of peperite in the Sanjiang Orogenic Belt in western Yunnan, China. Issue 1 (November 2019) - Cheng, Xianfeng; Zuo, Qionghua; Peng, Mingxing; Liu, Deli; Li, Xingtao; Ma, Wei; Na, Zhengqing
Abstract: Jamda-Weixi continent marginal arc belt is an important component to understand the evolution of Paleotethyan. For the first time, the occurrence of peperite is being reported at the bottom of Pantiange Formation in western Yunnan, China. Two types of peperites have been identified, namely fluidal peperite and blocky peperite. LA-ICP-MS U–Pb dating results (253.6±0.7Ma) of dacitic lava showed that the peperite was formed during the late Permian. The peperite was formed during the alternation of active period and quiet period of the volcano in an apparent shallow ocean margin.